Enhanced Mechanical and Fatigue Properties In AA5052 Via TiO_2 Nanoparticles Addition Sintering Temperature (ST) - Zahraa Kadhim; Hussain Alalkawi; Ahmed Reja (Engineering and Technology Journal, 2021)
The goal of the present work is to study the effect of different sintering temperatures (900, 1000 and 1100 ) on fatigue and mechanical characteristics of the metal matrix AA5052 reinforced with 5% of TiO2 nanoparticles. The stir casting process is used for manufacturing of AA5052/TiO2 nanocomposite. The mechanical characteristics of nano composites have been obtained at ambient temperature. The results of mechanical properties showed that the best enhancement in hardness (HB), ultimate tensile strength (UTS) and yield strength (YS) is occurred in nanocomposite with 1000  sintering temperature (ST). However, the fatigue test results showed that the samples manufactured under 1000  (ST) have longer fatigue life compared to other materials with different sintering temperatures. The endurance fatigue strength is improved by 7.2% compared to metal matrix. The experimental results showed that the microstructure image of 1000  (ST) composite has uniformly distributed of TiO2 in AA5052 matrix.